Predicting and Decreasing Bladder Tumor Recurrence Following Nephroureterectomy - Miyagi, Hiroko; Di Valerio, Elizabeth A.; O’Malley, Padraic; Brisbane, Wayne G.; Su, Li-Ming; Crispen, Paul L. (Frontiers in Urology, 2022)
Following radical nephroureterectomy for upper tract urothelial carcinoma, bladder tumor recurrence is a common event occurring in up to 22-47% of cases within the first post-operative year. In this review, we summarize the current knowledge on predictors of bladder tumor recurrence after radical nephroureterectomy and methods for reducing the risk of bladder tumor recurrence. Risk factors can be classified as modifiable and non-modifiable. Of these, the treating urologist has the greatest potential to decrease bladder tumor recurrence by focusing on treatment specific risk factors. Procedures which may decrease the risk of bladder tumor recurrence include limiting diagnostic ureteroscopy with biopsy to cases with equivocal diagnosis, use of perioperative intravesical chemotherapy, and complete distal ureterectomy with bladder cuff excision. Ongoing studies evaluating the timing and choice of intravesical chemotherapy during/after radical nephroureterectomy may help to further reduce bladder tumor recurrence in the future.